Expression of genes encoding the calcium signalosome in cellular and transgenic models of Huntington's disease - Czeredys, Magdalena; Gruszczyńska-Biegała, Joanna; Schacht, Teresa; Methner, Axel; Kuznicki, Jacek (Frontiers in Molecular Neuroscience, 2013)
Huntington’s disease (HD) is a hereditary neurodegenerative disease caused by the expansion of a polyglutamine stretch in the huntingtin (HTT) protein and characterized by dysregulated calcium homeostasis. We investigated whether these disturbances are correlated with changes in the mRNA level of the genes that encode proteins involved in calcium homeostasis and signaling (i.e., the calciosome). Using custom-made TaqMan low-density arrays containing probes for 96 genes, we quantified mRNA in the striatum in YAC128 mice, a model of HD, and wildtype mice. HTT mutation caused the increased expression of some components of the calcium signalosome, including calretinin, presenilin 2, and calmyrin 1, and the increased expression of genes indirectly involved in calcium homeostasis, such as huntingtin-associated protein 1 and calcyclin-binding protein. To verify these findings in a different model, we used PC12 cells with an inducible expression of mutated full-length HTT. Using single-cell imaging with Fura-2AM, we found that store-operated Ca2+ entry but not endoplasmic reticulum store content was changed as a result of the expression of mutant HTT. Statistically significant downregulation of the Orai calcium channel subunit 2, calmodulin, and septin 4 was detected in cells that expressed mutated HTT. Our data indicate that the dysregulation of calcium homeostasis correlates with changes in the gene expression of members of the calciosome. These changes, however, differed in the two models of HD used in this study. Our results indicate that each HD model exhibits distinct features that may only partially resemble the human disease.